EDUKASI PEMBERIAN MAKAN BAYI DAN ANAK BALITA BAWAH GARIS MERAH DI POSYANDU WILAYAH KERJA PUSKESMAS JEMURSARI: Vol. 1 No.2 (2025) : JURNAL PENGABDIAN MASYARAKAT MERDEKA MEMBANGUN NEGERI (ABDIMERKA) - Zaidania, Nabila; Efina Amanda (STIKES BANYUWANGI, 2025)
Educational activities on infant and child feeding materials were carried out on September 27 2024 at 9.48 WIB at one of the BGM Posyandu in the Jemursari Community Health Center Working Area, specifically Jemurwonosari sub-district with a target number of 20 mothers under five under the red line. the results of the 2023 Indonesian Health Survey published by the Ministry of Health, the prevalence of stunting in Indonesia in 2022 will remain at 21.6 percent, according to the findings of the Indonesian Nutrition Status Survey, although there has been a slight decrease, namely around 2.8 percent from 2021. people's lack of knowledge parents related to nutritional preparation and parenting patterns during pregnancy and 1000 days after the child is born. One of the efforts to improve the nutritional status of children under five is the Posyandu program for Toddlers Below the Red Line in the card towards health with education to increase the knowledge of mothers of toddlers who have nutritional problems about feeding babies and children appropriately to support the growth of toddlers according to their age. The method used was counseling or education through lectures and discussions and it was found that there was an increase in the understanding of mothers of babies and toddlers after being given education, namely by 31%.